Fecal Dipeptidyl Peptidase-4: An Emergent Biomarker in Inflammatory Bowel Disease. Issue 3 (10th March 2021) - Pinto-Lopes, Pedro; Melo, Francisco; Afonso, Joana; Pinto-Lopes, Rui; Rocha, Cátia; Melo, Daniel; Macedo, Guilherme; Dias, Cláudia Camila; Carneiro, Fátima; Magro, Fernando; ,
Abstract : INTRODUCTION: Dipeptidyl peptidase-4 (DPP-4) is a membrane-bound glycoprotein that acts as a receptor but also exists in a soluble form. It has been recognized as a mediator of inflammation and considered a biomarker in inflammatory bowel disease (IBD). METHODS: We evaluated a prospectively recruited cohort, consisting of 101 patients with IBD, using validated clinical indexes; 22 patients with ulcerative colitis (UC) underwent endoscopic evaluation. Fecal DPP-4 (fDPP-4) levels were analyzed and correlated with clinical scores, Mayo endoscopic score (in UC patients), serum DPP-4, C-reactive protein, and fecal calprotectin. Immunohistochemical staining for DPP-4 in intestinal biopsies was also performed. RESULTS: When compared with remitters, median fDPP-4 levels were higher in patients with ileal Crohn's disease (CD) (7, 584 [1, 464–7, 816] vs 2, 104 [630–2, 676] ng/mL, P = 0.015) and lower in patients with UC exhibiting clinical activity (1, 213 [559–1, 682] vs 7, 814 [2, 555–7, 985] ng/mL, P < 0.001). Patients with UC presenting endoscopic activity also had lower levels than remitters (939 [559–1, 420] vs 7, 544 [4, 531–7, 940] ng/mL, P = 0.006). Fecal DPP-4 discriminated clinical activity from remission with areas under the curve of 0.76 (95% confidence interval [CI] 0.58–0.94, P = 0.015) and 0.80 (95% CI 0.68–0.93, P < 0.001) in CD and UC, respectively; it allowed to differentiate endoscopic activity in patients with UC, with areas under the curve of 0.84 (95% CI 0.63–1.00, P = 0.009). Immunohistochemical analysis revealed higher DPP-4 apical expression in UC remitters, but no statistically significant differences were revealed between patients with ileal CD. DISCUSSION: Our results suggest that fDPP-4 can be used as a biomarker of IBD activity, particularly in UC. The expression profiles in intestinal tissue might represent a functional compartmentalization of DPP-4 expression.